Academic Entrepreneurialism and The Entrepreneurial University Model and Policy Implication for Vietnam - Dinh, Toan Van (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 36 No 4, 2020)
The article describes entrepreneurship in higher education institutions, also known as academic entrepreneurialism, based on theoretical research and the analysis of an entrepreneurial university model. Thanks to the research of the model and in practice, it is indicated that in the context of university transformation in Vietnam, policies and mechanisms in higher education management should be improved so as to create an ecological environment to promote innovation and to form advanced university governance.